1987
DOI: 10.3928/0148-4834-19870901-06
|View full text |Cite
|
Sign up to set email alerts
|

The Use of the Watson-Glaser Critical Thinking Appraisal to Predict Success in a Baccalaureate Nursing Program

Abstract: No nationally available objective instrument is currently recognized as predictive of successful nursing program completion. Such a measure, available prior to program entry, might guide admissions procedures and be used to counsel applicants. This longitudinal descriptive-correlational study investigated the Watson-Glaser Critical Thinking Appraisal as a potential predictor of success as measured by a passing score on the NCLEX examination for nurse registration. From a southern Arizona po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(21 citation statements)
references
References 6 publications
3
17
1
Order By: Relevance
“…The results from this study serve to support the mixed findings from Hickman’s (1993) review; that concluded, like the longitudinal studies of Berger (1984), Bauwens & Gerhard (1987), Kintgen‐Andrews (1988) and Sullivan (1987) and the cross‐sectional studies of Brigham (1989), Dungan (1986) and Matthews & Gaul (1979), using the Watson–Glaser Critical Thinking Appraisal, that there were no significant gains in critical thinking. Additionally, and perhaps more interestingly, the mean score for each of the groups was low (less than 25% of the total possible score) and Group P, the new students, with little exposure to the academic process, had the highest scores.…”
Section: Discussionsupporting
confidence: 69%
“…The results from this study serve to support the mixed findings from Hickman’s (1993) review; that concluded, like the longitudinal studies of Berger (1984), Bauwens & Gerhard (1987), Kintgen‐Andrews (1988) and Sullivan (1987) and the cross‐sectional studies of Brigham (1989), Dungan (1986) and Matthews & Gaul (1979), using the Watson–Glaser Critical Thinking Appraisal, that there were no significant gains in critical thinking. Additionally, and perhaps more interestingly, the mean score for each of the groups was low (less than 25% of the total possible score) and Group P, the new students, with little exposure to the academic process, had the highest scores.…”
Section: Discussionsupporting
confidence: 69%
“…Results such as these are not unique and are congruent with previous North American studies, relating to critical thinking as an outcome of nursing education and using the WGCTA as an instrument (Matthews & Gaul 1979, Valiga 1983, Bauwens & Gerhard 1987, Fleeger 1987, Sullivan 1987, Kintgen‐Andrews 1988). Each found that programmes of nursing education had no significant effect on critical thinking ability as measured by the WGCTA.…”
Section: Discussionsupporting
confidence: 86%
“…Ketefian (1981) reported a significant relationship between nurse’s critical thinking ability and their level of moral reasoning. Bauwens & Gerhard (1987) and Gross et al (1987 ) reported significant relationships between scores on the Watson–Glaser Critical Thinking Appraisal and scores of baccalaureate students on the National Council Licensure Examination (NCLEX) scores. On the other hand there have been at least four studies that reported no significant relationships between critical thinking skills and clinical judgement ( Tanner 1977, Gordon 1980, Gunning 1981, Holzemer & Mclaughlin 1988).…”
Section: Literature Reviewmentioning
confidence: 99%